Exploring Political Participation and News Media Consumption on Communicative Culture in Pakistan - Memon, Sumera; Ishak, Mohd. Sobhi; Abdul Hamid, Norsiah binti (Javanologi: International Journal of Javanese Studies, 2017)
This article is taking a conceptual approach to test the influence of Family, School and Peer group communicative culture on political participation through news media use. Although the concept of news media effect on political participation is not new. Yet there is scarcity in empirical antecedents which  motivate  youth  behavior  of  consuming  news.    Moreover,  Situated  Learning  Theory  will underpin  the study to  understand  the  consequences  of  lack  of  political  participation. Lastly, this paper  offered  a  framework  to  guide  researchers,  policymakers  and  Election  Commission  of Pakistan on what factor is more influential to intersect youth towards the political domain and how to engender political participation of Pakistani youth.